English language learning and learner empowerment: a mixed-method study of pre-service English teachers’ narratives on language, power and identity - López Gándara, Yiyi (Onomázein, 2020)
It is widely acknowledged that the expansion of English has had a democratising effect: knowledge is now accessible to a larger number of people worldwide. However, it is also contended that the uncritical and unreflective teaching of English is contributing to reproducing power structures, accentuating inequalities among speakers. This article presents the results of a study carried out with 86 final-year students in the Degree of Primary Education (English) at the University of Seville. Working within the framework of critical research, and combining both quantitative and qualitative methods, this study analyses learners’ perceptions on communicative competence, on the factors that bear upon successful communication, and their capacity to identify and understand power relations in communicative interactions. Results show that communicative competence does not necessarily entail learner empowerment; learners are too worried about linguistic aspects and accuracy when they speak English; they aspire to a model—the native speaker—that they can never reach; and they are not aware of power inequalities, their origin and how they transpire in communicative situations. This analysis points to the need to include a critical component in English language teaching to equip learners to identify and tackle power asymmetries in communicative interactions.